Decolorization of azo dye and generation of electricity by microbial fuel cell with laccase-producing white-rot fungus on cathode. (15th February 2017) - Lai, Chi-Yung; Wu, Chih-Hung; Meng, Chui-Ting; Lin, Chi-Wen
Graphical abstract: Highlights: A laccase-producing fungus on cathode of MFC was used to enhance degradation of azo dye. Laccase-producing fungal cathodes performed better than laccase-free control cathodes. A maximum power density of 13.38 mW/m 2 and an >90% decolorization of acid orange 7 were obtained. Growing a fungal culture with continuous laccase production improved MFC's electricity generation. Abstract: Wood-degrading white-rot fungi produce many extracellular enzymes, including the multi-copper oxidative enzyme laccase (EC 1.10.3.2). Laccase uses atmospheric oxygen as the electron acceptor to catalyze a one-electron oxidation reaction of phenolic compounds and therefore has the potential to simultaneously act as a cathode catalyst in a microbial fuel cell (MFC) and degrade azo dye pollutants. In this study, the laccase-producing white-rot fungus Ganoderma lucidum BCRC 36123 was planted on the cathode surface of a single-chamber MFC to degrade the azo dye acid orange 7 (AO7) synergistically with an anaerobic microbial community in the anode chamber. In a batch culture, the fungus used AO7 as the sole carbon source and produced laccase continuously, reaching a maximum activity of 20.3 ± 0.3 U/L on day 19 with a 77% decolorization of the dye (50 mg/L). During MFC operations, AO7 in the anolyte diffused across a layer of polyvinyl alcohol-hydrogel that separated the cathode membrane from the anode chamber, and served as a carbon source to support the growth of, and production of laccase by, the fungal mycelium that was planted on the cathode. In such MFCs, laccase-producing fungal cathodes outperformed laccase-free controls, yielding a maximum open-circuit voltage of 821 mV, a closed-circuit voltage of 394 mV with an external resistance of 1000 Ω, a maximum power density of 13.38 mW/m 2, a maximum current density of 33 mA/m 2, and a >90% decolorization of AO7. This study demonstrates the feasibility of growing a white-rot fungal culture with continuous laccase production on the cathode of MFCs to improve their electricity generation and azo dye removal efficiency.